A subset of low-grade B cell lymphomas with a follicular growth pattern but without a BCL2 translocation shows features suggestive of nodal marginal zone lymphoma - van den Brand, Michiel (J Hematop, 2015)
In our consultation practice, it was noted that many cases that were considered to represent follicular lymphoma (FL) without a BCL2 translocation were ultimately classified as nodal marginal zone lymphoma (NMZL). This study set out to define recurrent morphological features of these cases. Thirty-three low-grade B cell lymphomas without a BCL2 rearrangement were studied for recurrent morphological features. These features were then applied on 20 randomly selected cases to verify if these criteria are able to distinguish between lymphomas with and without a BCL2 rearrangement, assigning them to one of five categories ranging from “certain FL” to “certain NMZL.” Highly recurrent morphological features were noted in the lymphomas without a BCL2 rearrangement, which were strongly overlapping with the morphological features of NMZL. All six cases that were assigned to the category of certainly FL or most likely FL indeed harbored a BCL2 rearrangement, whereas all 12 cases assigned to the category of most likely NMZL or certain NMZL had no BCL2 break. Of the two cases in the ambiguous category, one had received a final diagnosis of FL and the other of NMZL. This study raises the hypothesis that a subset of low-grade B cell lymphomas with a follicular growth pattern but without a BCL2 translocation actually represents NMZL. This is at present difficult to prove, because no gold standard is available to differentiate between NMZL and FL without a BCL2 rearrangement, so further investigations are needed.